Small aircraft for application in agriculture - Trindade, O.; Ribeiro, R. E.; Carmo, M. S. (My University, 2000)
This paper describes the ARARA Project, the current phase of its development and the results obtained. ARARA (Autonomous and Radio-Assisted Reconnaissance Aircraft) employs small-scale aircraft to replace the full-size aircraft in aerial reconnaissance and monitoring tasks. ARARA aircraft have a much lower acquisition/maintenance cost and do not need specialized personnel for their operation, allowing for the acquisition of more information, more frequently than the other methods used so far. It is intended primarily for crop management and for the monitoring of areas under ecological stress. The project has four phases, each one resulting in a fully functional system intended for a particular range of applications. The cost, complexity, and range of applications of ARARA systems increase from the first phase. The ultimate goal is a fully automatic system to perform autonomous missions based on real time decision taking supported by on-board image processing. Phase I was completed last year and the results showed the usability of ARARA I systems for agricultural applications. This paper describes the other phases. Phase II is under final tests and is further described in this paper. ARARA II aircraft have two on-board video cameras. A forward-looking video camera allows the pilot to control the aircraft while a downward-looking camera allows an accurate identification of the area of interest that can be filmed on video or photographed by a digital/film camera. Preliminary results from the test phase demonstrate the functionality of ARARA II systems, and their extended applicability over phase I systems.
Keywords: Aerial photography; Crop management; Small-scale aircraft